2021
DOI: 10.1007/s10854-021-06545-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of triboelectricity in colossal-surface-area-lanthanum oxide nanocrystals synthesized via low-temperature hydrothermal process

Abstract: Triboelectric nanogenerators (TENGs) have marked their applications in various elds, most importantly, in medical devices. The electrical output of the TENGs mainly concentrated on parameters such as electrode separation distance, applied mechanical pressure, surface charge density, and overlapping surface-area. The surface-area of the active layer in TENGs plays a crucial role. Given this, the present contribution is the rst report on the utilization of lanthanum oxide (La 2 O 3 ) as an active material with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Because of the high-quality applications of La2O3 nanoparticles in many fields, it was successfully fabricated using various chemical and physical methods. Several studies have reported on the synthesis of La2O3 by various methods, including combustion, coprecipitation, hydrothermal, sol-gel, reflux, sonochemical, solvothermal, spray pyrolysis, and thermal decomposition methods [9][10][11][12][13][14][15][16][17]. The method election for the production of lanthanum nanoparticles is based on advantages.…”
mentioning
confidence: 99%
“…Because of the high-quality applications of La2O3 nanoparticles in many fields, it was successfully fabricated using various chemical and physical methods. Several studies have reported on the synthesis of La2O3 by various methods, including combustion, coprecipitation, hydrothermal, sol-gel, reflux, sonochemical, solvothermal, spray pyrolysis, and thermal decomposition methods [9][10][11][12][13][14][15][16][17]. The method election for the production of lanthanum nanoparticles is based on advantages.…”
mentioning
confidence: 99%